Application of Compatible Graph and Webster Methods for Traffic Light Arrangement in Jepara - Asih, Tri Sri Noor; Hidayati, Siti Nur; Mulyono, Mulyono; Rosyida, Isnaini (Universitas Muhammadiyah Mataram, 2023)
The problem of congestion has become a common problem that is often found on the highways, especially at the crossroads, without exception in Jepara Regency. The Mayong-Jepara Highway intersection is classified as a busy intersection that is full of vehicles during every departure and return hours, which are dominated by factory employees. Congestion often occurs at these intersections even though there are traffic lights that regulate the movement of vehicles. So, This study aims to find the solutions to congestion problems at Mayong-Jepara Highway intersection through compatible graph modeling and optimizing traffic light cycle time using the Webster method. Compatible graphs are used to determine traffic flows that are worked to move simultaneously without causing collisions, and that are used to carry out the graph weighting to determine the number of phases. The variables used in this applied research are the data on the number of vehicles, road width, and traffic light duration that taken directly in the field. Because the traffic density in the morning and afternoon is different for each intersection arm. Thus, the cycle time is determined in 2 sessions namely the morning and the afternoon. From the modeling of the compatible graph that has been weighted, it is obtained that the morning and afternoon sessions have 3 phases as the total which are then used to determine the traffic light cycle time. As a result, the cycle times for the morning session are 98 seconds, and the afternoon session is 155 seconds. The results were then simulated with PTV Vissim software and assessed to be quite effective in dealing with congestion and heavy traffic at the Mayong-Jepara Highway intersection especially in the afternoon session.